When dogs meow: An electrophysiological study of lexical–semantic processing in toddlers. (9th September 2021) - Manfredi, Mirella; Celebic, Corina; Daum, Moritz M.
Abstract: The goal of this study was to investigate lexical–semantic processing at an early phase of language development. Adults often communicate with children using infant ‐ directed speech that typically involves lexical and syntactic modifications such as onomatopoeias (Soderstrom, 2007). Here, we asked how and when children start to show an advantage for processing conventional linguistic forms, such as common nouns, and consequently decreasing sensitivity to onomatopoeias. We recorded event‐related brain potentials in children of two age groups (16–21 months and 24–31 months) and in an adult control group during the presentation of four conditions in which either common nouns or onomatopoeias were presented auditorily followed by a picture of an either congruent or incongruent object. We focused on the N400 effect, a more negative ERP response to incongruent compared with congruent semantic relations. The younger children showed an N400 effect only for onomatopoeic words, while the older children showed an N400 effect only for common nouns. The adults showed N400 effects for onomatopoeia and nouns. These different N400 effects suggest that onomatopoeia and common nouns are differently organized in children's semantic memory and that the acquisition of linguistic abilities affects and modifies semantic processing of different lexical information.